Increased Prevalence of Bipolar Disorders in Hidradenitis Suppurativa: More Than a Striking Coexistence? - Esme, Pelin; Maden, Aysenur (Dermatology Practical & Conceptual, 2022)
Introduction: Hidradenitis suppurativa (HS) is a chronic inflammatory skin disorder of the hair follicle characterized by intense discharge and pain. Recently, HS's intrinsic association with neuropsychiatric disorders has become a focus of attention, and bipolar disorder (BD) emerged as a relevant topic for such an association. Objective: This study aimed to evaluate BD's prevalence among HS patients and present the HS and BD overlap patients' demographics, detailed clinical characteristics with a discussion on aggravating factors. Patients-Method: A retrospective chart review of 247 HS outpatients (Group-1) identified eight patients with BD. The frequency of BD in HS patients is compared to psoriasis patients (Group-2) and controls (Group-3) in age- and gender-matched groups. The demographic and clinical features of the 8 patients revealing HS-BD co-existence were analysed. Results: BD (n=9) was the 7th most common co-morbidity in the HS cohort. The frequency of BD is detected as 3.6% in group 1, 0.7% (n=1) in group 2, and 0.6% (n=1) in group 3, respectively. Group 1 demonstrated an increased prevalence of BD compared to other groups (p=0.001). Of the 8 patients revealing HS and BD co-existence, 75% were active smokers, 62.5% were obese and 50% had metabolic syndrome. Conclusion: This study's results reveal that the prevalence of BD in HS patients is higher than psoriasis patients and controls. The pathogenetic mechanisms underlying BD and HS co-existence needs to be investigated further.